Indentifikasi Peluang Usaha pada Objek Wisata Pulau Kumayan oleh Masyarakat RT.12 RW.04 Kel. Surabaya Kec. Sungai Serut Kota Bengkulu - Suswati Nasution; Karona Cahya Susena; Nenden Restu Hidayah; Nirta Vera Yustanti; Yudi Ariantara (Universitas Dehasen Bengkulu, 2022)
The Kumayan Island tourist attraction is very close to the community members of RT.12 RW.04 Kel.Surabaya Kec.Sungai Serut, Bengkulu City, where the existence of this tourism object has aroused the interest of some people to open a business. The community of RT.12 realizes that the tourism sector is considered capable of having a positive impact on driving people's economic activities, although the pandemic is still hitting Indonesia and has an unfavorable impact on the tourism sector, it does not dampen the desire of people who want to open businesses around the Kumayan Island Bengkulu tourist attraction. In the Kumayan Island tourist attraction, there are already several tourism supporting businesses, especially businesses in the culinary fields, souvenirs and games. But the diversity has not been seen, the average business actor sells similar goods, so there is not enough variety. While one of the attractions of tourism is the culinary diversity that is around the location of the tourist attraction. For this reason, it is necessary to identify business opportunities. With the bridge by the Faculty of Economics Service Team, a training was held on the identification of business opportunities at the Kuwayan Island tourism object, Bengkulu City, in the Community of Rt.12. From the results of this training, the people who are participants gain new enthusiasm and can understand how to empower the potential and opportunities that exist so that they have an economic impact on the community and make the Kumayan Bengkulu Island tourist attraction even better in the future.